Computational design of peptide ligands to target the intermolecular interaction between viral envelope protein and pediatric receptor. (August 2017) - Xu, Darong; Bian, Hongliang; Cai, Jinlan; Bao, Daocheng; Jin, Qing; Zhu, Min; Zhang, Cuifeng; Tao, Tingting
Graphical abstract: Highlights: The interaction between the envelope protein and pediatric receptor is investigated in detail. A computational strategy is described to extract protein segments from the interaction. Several segments are identified as peptide inhibitors to target the interaction. Structural basis and energetic property of the protein–peptide binding are examined systematically. Abstract: The recognition and binding of viral envelope protein to pediatric receptor subverts the membrane-trafficking apparatus to mediate virion export in young children. Here, we described a successful computational design of peptide ligands to target the intermolecular interaction between the virus large envelope protein (LHB) and adaptin receptor (ADT). Based on the crystal structure of ADT in complex with an oligopeptide segment corresponding to the core binding site of LHB, a sequence-specific amino acid preference profile was determined systematically for the ADT-binding peptides using structural bioinformatics approach. With the information harvested from the profile, a genetic evolution procedure was run to improve the biological potency of a peptide population generated randomly from the LHB. A number of potential hits were obtained from the evolution, and four were measured to interact with ADT at micromolar level. A high-affinity hit peptide was then optimized according to computational structural analysis. It is revealed that a potent peptide can be divided into three regions, i.e. a negatively charged region at N-terminus, a hydrophobic core region in middle, and a small, polar region at C-terminal tail. In addition, the two termini of peptide are partially out of the active pocket of ADT, thus contributing moderately to the peptide binding.